Perkembangan Publikasi Ilmiah Makanan Halal di Negara Asia Analisa Bibliometrik: Penelitian Tahun 2001-2022 - Alfi Aulia; Muhammad Ruslianor Maika (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to find out the development of scientific publications related to the topic of Halal Food. Researchers used quantitative methods with bibliometric analysis. This research was conducted by searching through the Scopus database. id and use the keyword "Halal Food" with the categories of Article Titles, Abstracts, and Keywords. Then the results obtained were then extracted in the form of Bibtex and then processed and visualized using the Biblioshiny Web Interface, R Package. The results obtained are 998 scientific documents limited to only countries in Asia and with a span of 21 years (2001-2022), and using two types of documents, namely articles and conference papers. The results obtained are that scientific publications related to halal food have developed quite rapidly, marked by the large number of scientific publications on the topic of halal food.